Respon Pemberian Beberapa Dosis Pupuk Kotoran Kelelawar Terhadap Pertumbuhan dan Hasil Tanaman Cabai Rawit Hiyung pada Tanah Ultisol - Ayu Fitriani; Akhmad Rizali; Riza Adrianoor Saputra; Noorkomala Sari (Savana Cendana, 2022)
Hiyung chili is a type of chili found in Hiyung Village, Tapin District, South Kalimantan with a spiciness rate of 94,500 ppm. Bat manure is a fertilizer that contains elements of N, P, and K which are important for plant growth and development and are expected to increase nutrient content in the soil. This study aims to determine the effect and the best dosage of bat manure on the growth and yield of Hiyung chili on ultisol. Ultisol is a soil that has low organic matter, yellowish-red soil, acidic soil reaction, low base saturation, high Al content, low nutrient content such as N, P, and K. This study used a single factor CRD consisting of 5 treatment levels, namely k0 = 0 t.ha-1, k1 = 1 t.ha-1, k2 = 2 t.ha-1, k3 = 3 t.ha-1, k4 = 4 t.ha-1. The results of this study showed that giving several doses of bat manure fertilizer significantly affected plant growth, leaf size, fresh fruit weight, cropping, and crop production. The best bat manure doses to increase growth and yield of hiyung chili plants at a dose of 3 t.ha-1